Sobre o Status Morfofonológico e Prosódico das Formas Futuras em Português Arcaico (On the Morpho- Phonological and Prosodical Status of The Future Form in Archaic Portuguese ) - Massini-Cagliari, Gladis (2006)
This paper aims to discuss the morphophonological status of future tenses verbal forms in Archaic Portuguese. From the viewpoint of word formation, these verbal forms can be interpreted as the result of the regular inflexion of the base, or as compounds, formed by the main verb infinitive followed by an inflected auxiliary verb. Evidences are provided mainly by their prosodic behaviour, in comparison to other verbs. Although future forms are traditionally considered as simple verbal forms, their prosodic behaviour suggests that they are in fact compounds. Arguments that support this position are: the possibility of collocation of the clitic pronoun only in the middle future verbs; the variation with auxiliary initial verbal expressions (viverey or ey a viver, viveria or ia a viver), and the coordination of two verbs with only one future “mark”.KEYWORDS: Archaic Portuguese. Verbs. Compounds. Prosod. Stress.